Peran Notaris Dalam Pendirian Perseroan untuk Usaha Mikro Dan Kecil - Zulfikar, Andi Nilam Cahya; Sudantra, I Ketut (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 8 No 01 (2023)DO - 10.24843/AC.2023.v08.i01.p2, 2023)
The purpose of this study is to analyze the company for micro and small businesses in terms of the Job Creation Act and the Limited Liability Company Act and analyze the role of a notary in establishing a company for micro and small businesses. This research is a type of normative research, using a statutory approach and a comparative approach. The results of this study are that there are very significant differences and there are still many legal loopholes contained in the Employment Creation Act regulations regarding companies for micro and small businesses, and that the process of establishing companies for micro and small businesses does not require a notarial deed in accordance with the provisions of the Act. - Law Number 11 of 2020 concerning Job Creation where the establishment process is carried out by registering it electronically at the Ministry of Law and Human Rights without the need for a notary deed.